Аналіз сучасного стану хімічної обробки деталей, отриманих за допомогою 3D друку - Журавель, І. В. (ХНУРЕ, 2021)
The article describes the processing of ABS plastic with acetone, the advantages and disadvantages of such processing. The main properties of the effect of acetone on plastic were considered. compared the effects of acetone and dichloromethane. We also considered the principle of operation of an acetone bath, its advantages and disadvantages. They presented their own prototype of an acetone bath and a detailed description of the principle of its operation.
Keywords: хімічна обробка деталей; 3D друк